Driverless cars : on a road to nowhere - Wolmar, Christian (Perspectives (London, England), 2020)
"Driverless cars are the future. That is what the tech giants, the auto industry and even the government want us to think. Almost daily there are media stories about how we will soon all be able to rip up our driving licences, sit in the back seat and let the car take us around. But is this really going to happen? Christian Wolmar has dug behind the hype and found a very different story. We are nowhere near this driverless utopia. Indeed it may prove to be impossible to reach. And even if it were achievable, does anyone want it? Far from reducing traffic and pollution, millions of zombie cars on the roads would make them worse. Wolmar looks at the technical and other difficulties that make this driverless future a very uncertain proposition. He finds that it is the tech companies and the auto manufacturers who are desperate to get us out of the driving seat, and argues that far from making the roads safer, driverless cars may well make them more dangerous. This entertaining polemic sets out the many technical, legal and moral problems that obstruct the path to a driverless future, and debunks many of the myths around that future's purported benefits."--Publisher's website